Gene expression of immunoglobulin a and associates cytokines (IL-5, IL-6 and TGF-β) in intestinal mucosa of baby alpacas (Vicugna pacos) vaccinated with Clostridial antigen - Reyes Z., Joan (2017)
The aim of this study was to determine and compare the expression levels of IgA genes and associated cytokines IL-5, IL-6 and TGF-β in the intestinal mucosa of clinically healthy baby alpaca, that were orally vaccinated with a clostridial antigen. Ten unvaccinated baby alpacas (control) and 15 vaccinated (two doses with a seven-day interval) were used. Sampling was done seven days after the second dose. Likewise, two age subgroups (15-28 and 35-56 days of age at the time of sampling) were considered. Intestinal segments of 2 cm in length were taken from the middle portion of the jejunum and stored at -196 °C. Total RNA extraction was performed and the complementary DNA (cDNA) was synthesized by reverse transcription. Subsequently, real-time PCR was run using specific primers for IL-5, IL-6, TGF-β and exon 3 of IgA. Relative expression evaluation was performed using the 2-ΔΔÄCt method. Vaccinated animals with clostridial antigen had a greater expression of IgA (control: 275.3 fold, vaccinated: 710.2 fold more than the calibrator) (p = 0.005). The vaccinated alpacas of the 15-28 day subgroup expressed IL-5, IL-6 and TGF-β at 1.96, 4.78 and 2.87 fold higher than the calibrator, respectively, with a significant difference with the control group (p<0.05). It is concluded that the administration of clostridial antigen as an oral vaccine in baby alpacas in the first 14 days of age promotes a greater expression of the IL-5, IL-6, TGF-β and IgA genes at the intestinal mucosa level.